Formação contínua e práticas de leitura: o olhar do professor dos anos finais do ensino fundamental - Martins, Elcimar Simão (2014)
This thesis aimed to understand the relationship between lifelong learning and reading practices through the look of the teachers of the last years of elementary school, from Aracoiaba-CE. Considering that such teachers attending a training group, interested to know what they were doing in the impasse between the written and the lived between the written and the lived, in other words, between the training group and reading practices in primary education schools. This work results of the meeting and the redefinition of personal and professional author’s experiences allied to his process of continuous formation. Because of the complexity of the object of study, we opted for a qualitative research approach. The research-training was chosen by favoring the possibility of transformation of practices, considering the teacher of elementary school as essential to the investigation. Interviews were conducted with a sample of teachers, besides documentary sources were used. It was used the referential epistemology of practice, reflective teacher, teacher formation through the studies of Schön (2000, 1992), Nóvoa 1995), Imbernon (2009, 2010, 2011), Ribeiro (2010), Pimenta and Lima (2009), Ghedin, Almeida and Leite (2008), Pimenta and Ghedin (2002), Pimenta (2006), Lima (2012), Tardif (2013), Certeau (2012), among others. About the reading and readers practical, we used studies from Manguel (1997), Chartier (1996, 2007, 2009), Freire (1988), Silva (2012, 2005, 2000, 1997), Antunes (2009, 2003) were used, Lajolo (2008), Bamberger (2002), among others. The set of analyzes reveal that subjects consider the group as a legitimate learning space, revealing the importance of training as a collective project. Teachers emphasize the importance of sharing experiences with their pairs, the trust that has been generated in the group and the development of a process of reflection and investigation of reading practices developed at schools. The involvement of teachers in research-training group produced new knowledge that was linked to teaching practice. The offer of continuous training for teachers of basic education should not be at the mercy of the political will of a manager who holds the power in a timely manner. It should be thought and carried out as one continuous action, which does not suffer interruption with the change of who is ahead of decisions of education.